A Case Report and Review of the Literature of Adult Gastric Duplication Cyst - Samona, Scott (Case Rep Surg, 2015)
Gastrointestinal (GI) duplication cysts are a rare congenital disease. They may involve any level of the alimentary tract, but they most commonly involve the ileum, esophagus, and jejunum. Gastric duplication cysts represent approximately 4–8% of GI duplication cysts, the majority of which present in early childhood. We present a rare case of adult gastric duplication cyst in a 25-year-old female found to have abdominal mass on computed tomography imaging. There are several potential methods to diagnose gastric duplication cyst and treatment of choice is complete surgical resection.